Research on solar photovoltaic (PV) energy conversion system: an overview - Haque, A; Zaheeruddin (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
Solar Photovoltaic (PV) energy conversion system has drawn the tremendous attention of researchers in the past recent years. The concern related to global energy crisis and climate change threats from conventional sources of energy leads to look for alternate sources of energy. Solar energy is seen as a potential alternate source of energy as it is available globally in abundant. To develop an efficient and stable solar PV energy conversion various analysis are done by the researchers. It is analyzed at various facets like PV module characteristic and its arrangement, Power Electronics converters topologies, Maximum Power Point Tracking (MPPT) algorithm, stability of the system etc. This paper present an overview of the research going on in this area, focused on aspects mentioned above. This overview may be useful for further investigation to improve the system.